Location as a key factor for waste to energy plants - Silva, Maicon Gonçalves; Przybysz, André Luiz; Piekarski, Cassiano Moro (Journal of cleaner production, 2022)
The growing demand for energy, associated with the inherent challenges of urban solid waste management, makes many cities seek new treatment solutions, and among these, the Waste to Energy – WtE strategies stand out. However, the location of these plants still appears as a big challenge once it involves many factors in decision-making. In this way, the objective of this study is to identify the most relevant criteria for defining the ideal location for WtE plants and to point out the tools and methods most used in this process. To this end, a bibliographic review was carried out to find the main references on the subject. The results show that the place's definition is complex and considers criteria of different natures - economic, social, legal, and environmental -. Among these, those of an economic nature are the most recurrent and, in general, deal with issues related to the costs of installation and operation of the WtE plant, like costs related to the transport of residues, availability of residues, and easy access to road infrastructure. In turn, although with less recurrence, the social, legal, and environmental criteria also show their importance in the decision-making process. Among these, the most recurrent were: social (distance to urban centers, acceptance by the population, and strengthening of the local economy), legal (land use), environmental (the minimum distance to water bodies, the topographical characteristics of the area, and the minimum distance to protected areas). Considering the tools and analysis techniques, the Geographic Information System - GIS and Analytic Hierarchy Process - AHP methods were the most used, appearing respectively in about 40% and 30% of the analyzed studies. •Highlights the most recurrent criteria in the literature for the selection of the WtE plant installation site.•Highlights the role of MSW energy recovery for integrated waste management.•Points out the most applied multicriteria tools and methods in WtE plant installation projects.•It highlights that economic factors are more recurrent in the process of defining the location of installation of WtE plants.•It shows that environmental, legal, and social factors are more considered when making a decision.